Metagenomic next-generation sequencing promotes pathogen detection over culture in joint infections with previous antibiotic exposure - Gao, Zongyan; Zheng, Wendi; Zhang, Meng; Gao, Yanhua; Huang, Jincheng; Chen, Xiao; Dai, Zhipeng; Song, Zhenyu; Feng, Jiawei; Cao, Qianqian (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveTo investigate the diagnostic value of metagenomic next-generation sequencing (mNGS) in detecting pathogens from joint infection (JI) synovial fluid (SF) samples with previous antibiotic exposure.MethodsFrom January 2019 to January 2022, 59 cases with suspected JI were enrolled. All cases had antibiotic exposure within 2 weeks before sample collection. mNGS and conventional culture were performed on SF samples. JI was diagnosed based on history and clinical symptoms in conjunction with MSIS criteria. The diagnostic values, including sensitivity, specificity, positive/negative predictive values (PPV/NPV), and accuracy, were in comparison with mNGS and culture.ResultsThere were 47 of the 59 cases diagnosed with JI, while the remaining 12 were diagnosed with non-infectious diseases. The sensitivity of mNGS was 68.1%, which was significantly higher than that of culture (25.5%, p<0.01). The accuracy of mNGS was significantly higher at 71.2% compared to the culture at 39.0% (p <0.01). Eleven pathogenic strains were detected by mNGS but not by microbiological culture, which included Staphylococcus lugdunensis, Staphylococcus cohnii, Finegoldia magna, Enterococcus faecalis, Staphylococcus saprophytics, Escherichia coli, Salmonella enterica, Pseudomonas aeruginosa, Acinetobacter pittii, Brucella ovis, andCoxiella burnetii. Antibiotic therapy was adjusted based on the mNGS results in 32 (68.1%) patients, including 12 (25.5%) and 20 (42.6%) patients, in whom treatment was upgraded and changed, respectively. All JI patients underwent surgery and received subsequent antibiotic therapy. They were followed up for an average of 23 months (20-27 months), and the success rate of treatment was 89.4%. Out of the 33 patients who had positive results for pathogens, reoperation was performed in 1 case (3.03%), while out of the 14 cases with negative results for both mNGS and cultures, reoperation was performed in 4 cases (28.6%).ConclusionsmNGS has advantages over conventional culture in detecting pathogens in SF samples from JI patients previously treated with antibiotics, potentially improving clinical outcomes.